Criteria, Indicators and Levels of Formation of Professional Training of Future Specialists in the Agricultural Sector on the Basis of Praxeological Approach - Natalia Oliinyk (Pedagogical Discourse, 2020)
The article reveals the criteria for the formation of professional training of future specialists in the agricultural sector. Based on the analysis of scientific sources, it was found that the criterion can be defined as a set of key indicators that reveal the norm, the highest level of development of appropriate quality, and the indicator as a component of the criterion is a typical and specific manifestation of one of the significant aspects. availability of quality, to draw a conclusion about the level of its development.According to the structure of professional training of future specialists in the agricultural sector, the components are defined: content, operational and personal development, and the criteria are identified: cognitive, activity and development. Cognitive criterion is determined by such indicators as understanding the essence, content, goals and objectives of training, possession of a system of professionally important knowledge, familiarity with the methods and ways of performing future production tasks. The activity criterion is characterized by the formation of professional skills of future specialists in the agricultural sector, mastering the methods, techniques and experience of independent production tasks, the ability to exercise self-control, self-analysis and self-assessment of future work. The development criterion is revealed in such indicators as the formation of professionally important qualities, awareness of the importance of their future profession, the desire to improve professionalism, development of professional competencies, mobility, self-improvement and self-development. The definition of criteria and indicators made it possible to identify three levels of professional training of future specialists in the agricultural sector on the basis of a praxeological approach, in particular, low, medium, high.It should be noted that the defined indicators, criteria and levels will allow to comprehensively assess the formation of professional training of future specialists in the agricultural sector.